Carbapenemases in Enterobacteriaceae: Detection and Antimicrobial Therapy - Cui, Xiaoyan; Zhang, Haifang; Du, Hong (Frontiers in Microbiology, 2019)
Carbapenem-resistant Enterobacteriaceae (CRE) have spread rapidly around the world in the past few years, posing great challenges to human health. The plasmid-mediated horizontal transmission of carbapenem-resistance genes is the main cause of the surge in the prevalence of CRE. Therefore, the timely and accurate detection of CRE, especially carbapenemase-producing Enterobacteriaceae, is very important for the clinical prevention and treatment of these infections. A variety of methods for the rapid detection of CRE phenotypes and genotypes have been developed for use in clinical microbiology laboratories. Because the choice of antibiotics is necessarily limited, CRE infections are often treated with combination therapies. Moreover, novel drugs and emerging strategies for optimizing their activity and safety during treatment are still in various stages of development.